Cain and Abel in text and traditio n Jewish and Christian interpretations of the first sibling rivalry - Byron, John, 1967- (Themes in Biblical Narrative, 2011)
The story of Cain and Abel narrates the primeval events associated with the beginnings of the world and humanity. But the presence of linguistic and grammatical ambiguities coupled with narrative gaps provided translators and interpreters with a number of points of departure for expanding the story. The result is a number of well established and interpretive traditions shared between Jewish and Christian literature. This book focuses on how the interpretive traditions derived from Genesis 4 exerted significant influence on Jewish and Christian authors who knew rewritten versions of the story. The goal is to help readers appreciate these traditions within the broader interpretive context rather than within the narrow confines of the canon.